Fundamentals of Entrepreneurship (ENT300) : Cheezychics / Ezmith Ujang Syah Khairulhizam ... [et al.] - Khairulhizam, Ezmith Ujang Syah; Ahmad, Mohd Ridwan; Saimon, Nur Shafina; Mohammad Suhaili, Nur Suhadda; Abdul Hamid, Siti Nurhamizah (2019)
“Cheezychics” is located in Kota Samarahan, Sarawak that near to University area (between UNIMAS and UITM). We pick this location because our target markets is students. The location is a well-known place and it easy to find it. Our business focusing more to selling a popcorn chicken with the cheese as our main source. The popcorn chicken is a chicken breast that been cut into a small pieces that come with a cheese source with it. We provide with lot of options of source. Which is garlic cheese source, spicy cheese source, sweet and sour source, spocky swicy source, kimchi source and mayo cheese source. We using a cheese as our main ingredients of source because nowadays people like to eat a lot of thing with cheese and lot of students like it.